Promoting longevity by maintaining metabolic and proliferative homeostasis. - Wang, L.; Karpac, J.; Jasper, H. (Journal of Experimental Biology, 2014)
Aging is characterized by a widespread loss of homeostasis in biological systems. An important part of this decline is caused by age-related deregulation of regulatory processes that coordinate cellular responses to changing environmental conditions, maintaining cell and tissue function. Studies in genetically accessible model organisms have made significant progress in elucidating the function of such regulatory processes and the consequences of their deregulation for tissue function and longevity. Here, we review such studies, focusing on the characterization of processes that maintain metabolic and proliferative homeostasis in the fruitfly Drosophila melanogaster. The primary regulatory axis addressed in these studies is the interaction between signaling pathways that govern the response to oxidative stress, and signaling pathways that regulate cellular metabolism and growth. The interaction between these pathways has important consequences for animal physiology, and its deregulation in the aging organism is a major cause for increased mortality. Importantly, protocols to tune such interactions genetically to improve homeostasis and extend lifespan have been established by work in flies. This includes modulation of signaling pathway activity in specific tissues, including adipose tissue and insulin-producing tissues, as well as in specific cell types, such as stem cells of the fly intestine.